Effect of guided-discovery technique on Colleges of Education Social Studies students’ learning outcome - Abdulsalam Alliyu Ayodele; Olokooba Issa Nasiru (Journal of Education and Learning (EduLearn), 2021)
This study examined the effect of Guided-Discovery (GD) technique on Colleges of Education Social Studies students’ learning outcome in Nigeria. The study employed 2x2x2 randomized research design. A total of 100 students participated in the study, consisted of 50 GD and 50 Lecture Technique. Social Studies Performance Tests (SSPT) was used to collect data. It was designed using National Commission for Colleges of Education curriculum and validated by four Social Studies experts. The reliability value of 0.82 was obtained for the instrument using Cronbach Alpha. ANOVA and t-test were used for data analyses. This study found that GD technique of teaching Social Studies was next in producing higher significant effect in students’ learning outcome than LT. Gender has no significant interactive effect on students’ learning outcome in Social Studies. The mode of entry had no significant interactive effect in the learning outcome of Colleges of Education Social Studies Students. The study concluded that GD was found to be more effective in enhancing Social Studies Students’ learning outcome in Colleges of Education. It was recommended that GD technique should be used in teaching Social Studies in Colleges of Education.